KAJIAN SINKRONISASI PERENCANAAN BLOK PEMBERDAYAAN MASYARAKAT PADA KPHP MODEL SINTUWU MAROSO KABUPATEN POSO - Agustina, Nadine Sandra (JSTT, 2014)
The aim of the research was to synchronize the planning of community empowerment block using at PFMU of Sintuwu Maroso Model with factual condition in field and to analyze community responses on the planning of community empowerment block at PFMU of Sintuwu Maroso Model management. Community population were those who settle around the community empowerment block. Community forest at Kilo and Buyumpondoli villages were also sampled.  The respondent number was 50 people who lived around the area of HKm and village forest.  Data were analyzed using comparison analysis, land cover analysis, and the likert scale of 1, 3, and 5.  The research results showed that the community forests at both Kilo and Buyumpondoli villages are suitable for Hkm and village forest. The land of Kilo village Hkm and Buyumpondoli village forest were dominantly covered by dry land such as plantation and bushes.  Based on the likert scale, the criteria for the community empowerment block were that RKTN/RKTP and RKTK should be directed toward forest management at small scale 198 (79%); forest with low product 228 (91%); non forest area 236 (94%); HKm, village forest, and HTR  permit 142 (56%), area close to community 250 (100%); possibility of RKTN/RKTP/RKTK to be included in either rehabilitation region or  big/small scale forest region 144 (57%); and the community responses 220 (88%).  It can be concluded that the criteria and the community responses are classified high.